2020
DOI: 10.3390/ijms21218275
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Androgen-ZIP9 Signaling and Notch Pathway in Rodent Sertoli Cells

Abstract: Our recent study demonstrated altered expression of Notch ligands, receptors, and effector genes in testes of pubertal rats following reduced androgen production or signaling. Herein we aimed to explore the role of nuclear androgen receptor (AR) and membrane androgen receptor (Zrt- and Irt-like protein 9; ZIP9) in the regulation of Notch pathway activation in rodent Sertoli cells. Experiments were performed using TM4 and 15P-1 Sertoli cell lines and rat primary Sertoli cells (PSC). We found that testosterone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
(82 reference statements)
2
4
0
Order By: Relevance
“…We have recently reported that testosterone increases the activity of the Notch pathway in rat and mouse Sertoli cells, upregulating the expression of Notch1 intracellular domain and the effector genes Hes1 and Hey1 [46]. In light of these data, the results of the present study suggest that enhanced Notch pathway activity following testosterone exposure may be, at least to some extent, associated with reduced expression of DLL1 or JAG1 proteins, which potentially prevents cis-inhibitory interactions within Sertoli cells.…”
Section: Discussionsupporting
confidence: 58%
“…We have recently reported that testosterone increases the activity of the Notch pathway in rat and mouse Sertoli cells, upregulating the expression of Notch1 intracellular domain and the effector genes Hes1 and Hey1 [46]. In light of these data, the results of the present study suggest that enhanced Notch pathway activity following testosterone exposure may be, at least to some extent, associated with reduced expression of DLL1 or JAG1 proteins, which potentially prevents cis-inhibitory interactions within Sertoli cells.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the dorso-ventral axis formation pathway, NOTCH genes are also involved in signaling pathways. There was an interaction between androgen and the Notch signaling pathway in Sertoli cells ( Kamińska et al, 2020 ). Additionally, the Notch signaling pathway significantly affects the reproductive organ development of male mice ( Lupien et al, 2006 ) and may be an important pathway for the physiological regulation of Sertoli cells, with these changes potentially leading to disturbances in the response of Sertoli cells to androgens ( Kamińska et al, 2020 ); however, differences in the Notch signaling pathway were not significant in this study.…”
Section: Discussionmentioning
confidence: 99%
“…C: cells untreated; C+: cells treated with sodium nitroprusside; Bj-CV: crude venom of Bothrops jararaca snake; Bj-PF: peptide fraction obtained from crude venom. Gu et al, 2022;Kamińska et al, 2020). For this reason, we used an in vitro culture model of 15P-1 Sertoli cells to study the effects of Bj-PF on mitochondrial metabolism and NO generation in this cell type of the seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 99%